2020
DOI: 10.20945/2359-3997000000282
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Lesions with Papillary Nuclear Characteristics: Differences in Chromatin Detected by Computerized Image Analysis

Abstract: Objective: Follicular lesions of the thyroid with papillary carcinoma nuclear characteristics are classified as infiltrative follicular variant of papillary thyroid carcinoma-FVPTC (IFVPTC), encapsulated/ well demarcated FVPTC with tumour capsular invasion (IEFVPTC), and the newly described category "non-invasive follicular thyroid neoplasm with papillary-like nuclear features" (NIFTP) formerly known as non-invasive encapsulated FVPTC. This study evaluated whether computerized image analysis can detect nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological 9–11,14 and histological 15–17 samples. Studies with histological samples are more common in the literature 15–17 .…”
Section: Discussion/conclusionsupporting
confidence: 85%
See 3 more Smart Citations
“…We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological 9–11,14 and histological 15–17 samples. Studies with histological samples are more common in the literature 15–17 .…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…This is consistent with the concept of nuclear size as an important feature for discriminating benign from malignant cells. 13 We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological [9][10][11]14 and histological [15][16][17] samples. Studies with histological samples are more common in the literature.…”
Section: Ta B L Esupporting
confidence: 82%
See 2 more Smart Citations
“…Studies with larger samples would probably include NIFTP cases ( 23 ), which were not found in our group of patients and could have nuclear alterations but turn out to be 'non-malignant' in the final histological examination. In this sense, we compared recently the histological material of NIFTP, infiltrative FVPC, and encapsulated/well-demarcated FVPC with tumor capsular invasion, using CANI and observed nuclear textural differences between NIFTP and infiltrative FVPC but not between the former and encapsulated/well-demarcated FVPC ( 24 ). In addition to significantly larger samples, it would also be interesting to apply this model to other Bethesda categories, such as benign.…”
Section: Discussionmentioning
confidence: 99%